Kangaroo protocol as a sensor: monitoring parameters of wireless sensor networks = Protokół Kangaroo jako sensor: monitorowanie parametrów Bezprzewodowych Sieci Sensorowych - Maj, Jakub; Piotrowski, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
The current development of Wireless Sensor Networks (WSN) has made them capable of handling large amounts of nodes and data, often using network layer protocols enabling multi-hop transmission. This approach means that the network protocol itself can provide a lot of valuable information. This article presents the multi-hop WSN protocol, which, in addition to data transmission, is also classified as a sensor, providing valuable information about the state of connections in the network, the status of packets, information about neighboring nodes or the paths through which packets are sent.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne